ZnO Interface Modified LiNi0.6Co0.2Mn0.2O2 Toward Boosting Lithium Storage. Issue 4 (13th June 2020) - Li, Yunyan; Li, Xifei; Hu, Junhua; Liu, Wen; Maleki Kheimeh Sari, Hirbod; Li, Dejun; Sun, Qian; Kou, Liang; Tian, Zhanyuan; Shao, Le; Zhang, Cheng; Zhang, Jiujun; et al.
Abstract : In this work, an amorphous ZnO was coated on LiNi0.6 Co0.2 Mn0.2 O2 (NCM) using a sol‐gel strategy method. The NCM coated with 1 wt.% ZnO and a thickness of about 3 nm exhibits an improved cycling performance, accompanied by a lower capacity fading (from 194.8 to 133.8 mAh g −1, i.e., 68%) than that of the pristine one (i.e., only 34%) after 300 cycles at 0.2 C. The cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) indicate that the ZnO coating can improve extraction/insertion of Li + and inhibit the increase in impedance of the NCM cathode material. This approach may benefit the performance improvement of the Ni‐rich cathode materials in Lithium‐ion batteries (LIBs). Abstract : Ultra‐thin ZnO films were successfully designed onto NCM. Lithium‐ion cells assembled with ZnO‐coated NCM cathode materials showed better capacity retention than cells with the bare materials. The improved electrochemical performance can be attributed to the protection of the surface of NCM and suppression of the side reactions between NCM and the electrolyte, thus reducing the impedance.